Phenological documentation of Lantana camara L. using modified BBCH scale in relation to climatic variables - Kumar, Abhishek; Singh, Sanjay; Chand, Harish Bahadur; Kumar, Rahul (Plant Science Today, 2022)
Lantana camara L. (Verbenaceae) is cultivated as an ornamental and hedge plant in many countries which is native to American tropics. It’s introduction to the Indian subcontinent dates back around 200 years ago. It is an invasive alien species that has a negative impact on native biodiversity. It is evident that management of L. camara is crucial for the conservation of biodiversity. Studying its phenological characteristics as they adapt to environmental circumstances through time and space will aid in the development of management goals and strategies. This study uses BBCH scale firstly to describe the phenology of L. camara, which is represented by nine Phenological Growth Stages (PGS) in response to environmental conditions during a 32-month period in Dehradun, Uttarakhand, representing its growth. To standardise morphological traits and the phenological observation, photographs of certain significant developmental stages on L. camara in addition to the descriptions have been illustrated. Researchers can utilise this uniform labelling method as a tool to help with weed management efforts. Phenological studies of this invasive weed species may be employed for tracking the gradual impact of climate change on biodiversity and its effect on the key phenological events in the lifecycle.